DAMPAK LINGKUNGAN SOSIAL TERHADAP PERUBAHAN PERILAKU REMAJA PEREMPUAN DI DESA AMMAT KECAMATAN TAMPAN’AMMA KABUPATEN KEPULAUAN TALAUD - Sapara, Mensi M.; Lumintang, Juliana; Paat, Cornelius J. (Universitas Sam Ratulangi, 2020)
The study aims to understand more deeply about the social environment impact on changing the behavior of young womwn in the village Ammat. By referring to the focus of research which is what changes in behavior in young women are caused by the impact of the social environment of case studies (Village Ammat, Sub-district. Tampan’Amma, District. Talaud).Studies employ qualitative methods with descriptive types that emphasize more than depictions of objects examined in the light of the facts. The indentifications of informants was done in a way purposive sampling which suggests that the indentification of a deliberate informant with certain criteria is thought to be able to provide information related to the research problem of collection techniques used in this research observation, interview, and documentation techniques. The study explained that a young woman who experienced a change in behavior from a social environment had a profound impact on her friend’s environment. Keywords: impact, social environment, change, behavioral, teenage girls